2018
DOI: 10.3126/ejdi.v21i1-2.19023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dividend Payment on Stock Prices of Commercial Banks in Nepal: Panel Approach

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…Thus, the firm's management should try to increase stock dividend rather than cash dividend to increase their stock market price and their value of the firm. The result of this study is compactable with the result of Khan (2012) and Bhattarai (2016). They found that stock dividend has significant positive impact on stock market price.…”
Section: Resultssupporting
confidence: 81%
“…Thus, the firm's management should try to increase stock dividend rather than cash dividend to increase their stock market price and their value of the firm. The result of this study is compactable with the result of Khan (2012) and Bhattarai (2016). They found that stock dividend has significant positive impact on stock market price.…”
Section: Resultssupporting
confidence: 81%
“…This implies that the optimal dividend payout is the one that maximizes the total value of the company. The obtained result is familiar to the results by Benaruzi (1997), Bhattarai (2016), Singh and Tandon Full text can be downloaded https://www.nepjol.info/index.php/craiaj & http://www.craiaj.info/ (2019) and contradicts with that of Ali and Chowdhury (2010)which conveys that dividend announcement does not impact on share the price of banks.…”
Section: Discussionmentioning
confidence: 51%
“…To make secure and lucrative investments, investors must thoroughly review the available data on companies. Bhattarai (2016) conducted a causal comparative research study to examine the effect of dividend payment on the stock prices of banks in Nepal. According to the study, it has been found that dividend per share has a noteworthy and optimistic influence on the share price of commercial banks in Nepal.…”
Section: Nepali Studiesmentioning
confidence: 99%
See 1 more Smart Citation